A crowdsourcing open platform for literature curation in UniProt. - Yuqi Wang; Qinghua Wang; Hongzhan Huang; Wei Huang; Yongxing Chen; Peter B McGarvey; Cathy H Wu; Cecilia N Arighi; UniProt Consortium (PLoS Biology, 2021)
The UniProt knowledgebase is a public database for protein sequence and function, covering the tree of life and over 220 million protein entries. Now, the whole community can use a new crowdsourcing annotation system to help scale up UniProt curation and receive proper attribution for their biocuration work.